To Evaluate the Performance based on Delay and Jitter of Wired VoIP using a network of assorted number of Routers and Hosts. - Kadam, PN; Gangarde, RR (International Journal of Computer Sciences and Engineering, 2025)
In this paper, we study experimentally the performance of VoIP on wired communication with varied combination of Routers and hosts. We concentrate on two factors of QoS – Delay and Jitter. NS3 simulator is used to study the pattern and effect on the two factors by varying the number of Routers and hosts in the given setup. By this study the user can decide on what combination is best for his application and what factors can be compromised and which factors can be enhanced. Also, we have concluded by giving a glimpse of using the results of this experiment for QoE. The study can further be extended to including all the factors that come under QoS.